Praktik Foto Prewedding di Kabupaten Aceh Utara : Analisis Fiqh Syāfi‘Iyyah Dan Qanun Aceh Nomor 6 Tahun 2014 Pasal 1 Ayat 24 Tentang Ikhtilat - Afrizal M. Ali; Husni Husni; Safriadi Safriadi (Siyasah Wa Qanuniyah, 2026)
The development of the wedding industry in the digital era has given rise to a new tradition in the form of prewedding photography before the marriage contract. In North Aceh Regency, this phenomenon is no longer merely a documentation need but has transformed into a visual popular culture frequently published on social media, thereby triggering the issue of "virtual ikhtilat". This study aims to analyze the practice of prewedding photography in the North Aceh community based on the perspective of Fiqh Syāfi‘iyyah and Aceh Qanun Number 6 of 2014 concerning Jinayat Law. Using a qualitative method with a juridical-sociological approach, data were collected through observation, interviews, and document studies, then analyzed using triangulation techniques. The results show that the majority of prewedding practices contain elements of ikhtilāṭ, khalwat, and kasyf al-‘aurah. In the perspective of Fiqh Syāfi‘iyyah, this practice is strictly considered haram based on the principle of sadd al-dzarī‘ah. Under local positive law, this practice substantively fulfills the elements of violation of Article 1 Paragraph 24 of Aceh Qanun No. 6 of 2014, but its enforcement is hindered by cultural clashes and weak supervision. As a solution, this study recommends strengthening siyasah syar'iyyah through the formulation of Reusam Gampong (Village Regulations) and offers the technical instrument of "Prewedding Syar‘i". This concept separates interaction spaces and eliminates physical touch, making it an applicable operational standard without neglecting Islamic legal principles.